Late-Holocene: Cooler or warmer?. (September 2021) - Wanner, Heinz
Early studies on the evolution of glaciers argue that the warm Early Holocene transitioned into a Late-Holocene Neoglacial, with numerous glacial advances due to decreasing solar forcing in the boreal summer. The assumption of decreasing temperatures based on the glacier studies was supported by several proxy-based reconstructions as well as by simulations. Under the keyword "Holocene temperature conundrum" this fact is questioned. In particular, it is argued that the proxy studies are biased on time series dominated by a seasonal bias in the form of predominant summer temperatures (mainly marine). After a presentation of the facts, the weaknesses of both hypotheses (cooler or warmer) are briefly presented.